1996
DOI: 10.1002/(sici)1099-0496(199603)21:3<176::aid-ppul5>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pulmonary function and polysomnography in obese children and adolescents

Abstract: Obese adults have an increased prevalence of pulmonary disorders. Although childhood obesity is a common problem, few studies have evaluated the pulmonary complications of obesity in the pediatric population. We, therefore, performed pulmonary function tests (PFTs), polysomnography, and multiple sleep latency tests (MSLTs) in 22 obese children and adolescents [mean age, 10 2 5 (SD) years; 73% female; 184 5 36% ideal body weight], none of whom presented because of sleep or respiratory complaints. PFTs were norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0
12

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 4 publications
4
69
0
12
Order By: Relevance
“…However, studies on children have found conflicting results. Lung compliance, vital capacity, and residual volume in obese children are similar to those of non-obese children in the majority of the studies (23)(24)(25)(26) have confirmed reduced functional residual capacity and static lung volumes (12)(13)(14). The impact of obesity on respiratory functions in overweight, obese and morbidly obese children has not yet been fully determined.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, studies on children have found conflicting results. Lung compliance, vital capacity, and residual volume in obese children are similar to those of non-obese children in the majority of the studies (23)(24)(25)(26) have confirmed reduced functional residual capacity and static lung volumes (12)(13)(14). The impact of obesity on respiratory functions in overweight, obese and morbidly obese children has not yet been fully determined.…”
Section: Discussionmentioning
confidence: 85%
“…Inselman et al (13) found a reduced diffusion capacity and ventilatory muscle endurance among obese children. Marcus et al (26) found both restrictive and obstructive abnormalities on pulmonary function tests in obese children. Mallory et al (12) reported that obstructive abnormalities were the main problem in obese children.…”
Section: Discussionmentioning
confidence: 98%
“…22 In a small study of 22 obese children, 46% had abnormal polysomnograms and there was a positive correlation between degree of obesity and apnoea index. 23 Management of OSA in the obese child N Weight loss is the most effective long term treatment, but the least likely to take place. N Adenotonsillar hypertrophy is associated with OSA in both obese and non-obese patients.…”
Section: Obstructive Sleep Apnoeamentioning
confidence: 99%
“…[3][4][5][6][7] Similar data in the paediatric population are however, limited and conflicting. Marcus and colleagues, 8 in their study of 17 patients, found only two to have abnormal lung function. One had restrictive deficit and the other obstructive abnormality.…”
mentioning
confidence: 97%